'PUBLISH OR PERISH:' THE PITFALLS OF DUPLICATE PUBLICATION - Noè L.F.; Batten D.J. (My University, 2006)
Duplication of previously published text or figures in the scientific literature without adequate citation is plagiarism or, in the case of an author's own work, self-plagiarism. It breaches the ethical standards that are expected in science and threatens the integrity of scientific journals. Three examples of duplication are noted, one of which involves Palaeontology. Redundant publication lowers the quality of scientific literature, damages the good standing of journals, and reduces the intellectual impact of a study. Multiple papers on a particular theme are only acceptable if each builds significantly upon previous work and contains only as much background information as necessary to put the new data and observations into perspective. © 2006 The Palaeontological Association.
Keywords: PALAEONTOLOGY; PLAGIARISM; PUBLICATION ETHICS; SELF-PLAGIARISM